Relatório de Estágio Profissional "Aprender a Ser Professor em Contexto de Estágio" - Samuel de Medeiros Toste (2019)
This report illustrates the path of a preservice teacher during the practicum training in the Masters in Teaching Physical Education at the Faculty of Sport, Porto University. The practicum training is the culmination of the academic education, where the articulation of the knowledge acquired during the educational process with the demands of the teaching practice shows as the decisive period. The practicum took place in a school in the city of Praia da Vitória, which included students from the 3rd cycle of Basic and Secondary Education. The practicum group, with only a preservice teacher, was guided by a cooperating teacher from the school as well as a faculty supervisor. It was up to the preservice teacher to teach a class of the eleventh level of the Scientific- Humanistic Science and Technology course. The present document is structured in four fundamental parts: the personal framework, where some individual characteristics of the preservice teacher (the author) , his career as an athlete and student up to the time of writing and their expectations; the framing of professional practice, where the institutional context in which the practicum took place is described; the realization of professional practice, which describes the processes of teaching organization, management and learning; and the study about the motivation for the practice of Physical Education in function of the sex, the sport practice and the cycle of education. KEYWORD: